Extended anticoagulation treatment for cancer‐associated thrombosis—Rates of recurrence and bleeding beyond 6 months: A systematic review. (8th December 2021) - Moik, Florian; Colling, Meaghan; Mahé, Isabelle; Jara‐Palomares, Luis; Pabinger, Ingrid; Ay, Cihan
Abstract: Background: Patients with cancer‐associated venous thromboembolism (VTE) are recommended to receive treatment with therapeutic anticoagulation for at least 3–6 months. Little data exist on extended treatment beyond 6 months. Objective: To comprehensively summarize the best available evidence on incidence of recurrent VTE and major bleeding 6–12 months after the index event in patients with cancer‐associated VTE. Patients/Methods: We systematically screened biomedical databases (MEDLINE, Embase, CENTRAL) to identify studies reporting recurrent VTE and/or bleeding events between 6 and 12 months after a diagnosis of cancer‐associated VTE. Based on the observed heterogeneity in study design, setting, patient cohort characteristics, anticoagulation strategies, and outcome rates, no overall quantitative estimate of outcome rates was calculated. Results: We screened 2597 publications and identified 11 eligible studies matching predefined in‐/exclusion criteria, reporting on 3019 patients specifically during the 6‐ to 12‐month period post–index VTE. Overall rates of recurrent VTE in this timeframe varied substantially (1%–12%), with the highest risk observed in the patient subgroup with residual vein thrombosis present at 6 months randomized to receive no anticoagulation (13%–15%). Reported rates of major bleeding between 6 and 12 months were between 2% and 5%. Conclusions: In this systematic review, we provide a comprehensive and structured summary of the best available evidence on recurrence and bleeding risk between 6 and 12 months after cancer‐associated VTE. VTE recurrence remains common beyond 6 months and continuation of different anticoagulation strategies has an acceptable safety profile indicated by lower bleeding rates. These findings support guideline recommendations to continue anticoagulation treatment beyond 6 months in patients with active cancer.